Temporal trends and determinants of COVID-19 vaccine coverage and series initiation during pregnancy in Ontario, Canada, December 2020 to December 2021: A population-based retrospective cohort study. Issue 10 (3rd March 2023) - Fell, Deshayne B.; Török, Eszter; Sprague, Ann E.; Regan, Annette K.; Dhinsa, Tavleen; Alton, Gillian D.; Dimanlig-Cruz, Sheryll; MacDonald, Shannon E.; Buchan, Sarah A.; Kwong, Jeffrey C.; Wilson, Sarah E.; Håberg, Siri E.; et al.
Abstract: Background: Population-based COVID-19 vaccine coverage estimates among pregnant individuals are limited. We assessed temporal patterns in vaccine coverage (≥1 dose before or during pregnancy) and evaluated factors associated with vaccine series initiation (receiving dose 1 during pregnancy) in Ontario, Canada. Methods: We linked the provincial birth registry with COVID-19 vaccination records from December 14, 2020 to December 31, 2021 and assessed coverage rates among all pregnant individuals by month, age, and neighborhood sociodemographic characteristics. Among individuals who gave birth since April 2021—when pregnant people were prioritized for vaccination—we assessed associations between sociodemographic, behavioral, and pregnancy-related factors with vaccine series initiation using multivariable regression to estimate adjusted risk ratios (aRR) and risk differences (aRD) with 95% confidence intervals (CI). Results: Among 221, 190 pregnant individuals, vaccine coverage increased to 71.2% by December 2021. Gaps in coverage across categories of age and sociodemographic characteristics decreased over time, but did not disappear. Lower vaccine series initiation was associated with lower age (<25 vs. 30–34 years: aRR 0.53, 95%CI 0.51–0.56), smoking (vs. non-smoking: 0.64, 0.61–0.67), no first trimester prenatal care visit (vs. visit: 0.80, 0.77–0.84), and residing in neighborhoods with the lowest income (vs. highest: 0.69, 0.67–0.71). Vaccine series initiation was marginally higher among individuals with pre-existing medical conditions (vs. no conditions: 1.07, 1.04–1.10). Conclusions: COVID-19 vaccine coverage among pregnant individuals remained lower than in the general population, and there was lower vaccine initiation by multiple characteristics.